Measure of molecular diversity within the Trypanosoma brucei subspecies Trypanosoma brucei brucei and Trypanosoma brucei gambiense as revealed by genotypic characterization - Agbo, E.C.; Majiwa, Phelix A.O.; Classsen, E.J.H.M.; Roos, M.H. (Elsevier, 2001)
We have evaluated whether sequence polymorphisms in the rRNA intergenic spacer region can be used to study the relatedness c.' two subspecies of Trypanosoma brucei. Thirteen T. bnrcei isolates made up of 6 T. b. brucei and 7 T. b. gambiense were analyzed using restriction fragment length polymorphism (RFLP). By PCR-based restriction mapping of the ITS I-5.8S-ITS2 ribosomal repeat unit. we found a fingerprint pattern that separately identifies each of the two subspecies analyzed, with unique restriction fragments observed in all but f of the T. b. gambiense "human" isolates. Interestingly, the restriction profile for a virulent group 2 T. b. gambiense human isolate revealed an unusual RFLP pattern different from the profile of other human isolates. Sequencing data from four representatives of each of the two subspecies indicated that the intergenic spacer region had a conserved ITS- l and a variable 5.8S with unique transversions, insertions, or deletions. The ITS-2 regions contained a single repeated element at similar positions in all isolates examined. but not in 2 of the human isolates. A unique 4-by ; C3A} sequence was found within the 5.8S region of human T. b. gambiense isolates. Phylogenetic analysis of the data suggests that their common ancestor was a ronhuman animal pathogen and that human pathogenicity might have evolved secondarily. Our data show that cryptic species within the T. brucei group can be distinguished by differences in the PCR-RFLP profile of the rDNA repeat.